Third European Stroke Science Workshop. Issue 7 (July 2016) - Dichgans, Martin; Planas, Anna M.; Biessels, Geert Jan; van der Worp, Bart; Sudlow, Cathie; Norrving, Bo; Lees, Kennedy; Mattle, Heinrich P.
Abstract : Lake Eibsee, Garmisch-Partenkirchen, November 19 to 21, 2015: The European Stroke Organization convened >120 stroke experts from 27 countries to discuss latest results and hot topics in clinical, translational, and basic stroke research. Since its inception in 2011, the European Stroke Science Workshop has become a cornerstone of European Stroke Organization's academic activities and major highlight for researchers in the field. Participants include stroke researchers at all career stages who convene for plenary lectures and discussions, thus facilitating crosstalk among researchers from different fields. As in previous years, the workshop was organized into 7 scientific sessions each focusing on a major research topic. All sessions started with a keynote lecture that provided an overview on current developments and set the scene for the following presentations. The latter were short focused talks on a timely topic and included the most recent findings, including unpublished data. A new element at this year's meeting was a hot topic session in which speakers had to present a provocative concept or update sharply within 5 minutes. In the following, we summarize the key contents of the meeting. The program is provided in the online-only Data Supplement. Abstract : Supplemental Digital Content is available in the text.